Analisis Hukum Kepatuhan Industri Manufaktur terhadap Permenaker Nomor 5 Tahun 2018 : Tantangan Pengawasan dan Efektivitas Sanksi K3L - Yuliana Yuliana; Adella Dwi Agustina; Cindy Gracella Hutabarat; Muhamad Seip (Journal of Industrial Relations Studies, 2026)
This research analyzes the compliance of the manufacturing industry with Ministry of Manpower Regulation No. 5 of 2018 concerning Occupational Safety and Health in the Working Environment (K3L). Using a normative legal method, it was found that industrial compliance is often merely administrative and fails to penetrate the operational level. The main challenges lie in the low ratio of labor inspectors, the lack of technical specialization of supervisors, and legal sanctions that provide no deterrent effect for large corporations. The results conclude that the effectiveness of this regulation requires progressive fine reforms and the strengthening of supervisory functions through digitalization. Transforming the safety culture is crucial to bridging the gap between legal norms and field practicesnt